Effects of dietary postbiotic and inulin on growth performance, faecal microflora and IGF-I and GHR mRNA expression in broilers - Kareem, Karwan Yaseen; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi; Akit, Henny (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The study examined the effect of combinations of postbiotics and inulin on growth performance, faecal microflora, and pH, liver IGF-I and GHR mRNA expression in broiler chickens. A total of 288 one day old chicks were randomly into eight treatment groups viz basal diet without additive (negative control), basal diet feed + neomycin and oxytetracycline (positive control), T1=Basal diet + 0.3% postbiotic RI11, T2=Basal diet + 0.3% postbiotic RG14, T3=Basal diet + 0.3% postbiotic RI11 + 0.8% inulin, T4=Basal diet + 0.3% postbiotic RI11 + 1.0% inulin, T5=Basal diet + 0.3% postbiotic RG14 + 0.8% inulin, T6=Basal diet + 0.3% postbiotic RG14 + 1.0% inulin. Birds fed T3, T4 and T6 had higher (p<0.05) final body weight and total weight gain than did other treatments. Birds fed T3 had lower FCR which was significantly different from those fed negative control diet but was similar to other treatments. Postbiotic and inulin increased (p<0.05) faecal LAB at compared to negative control and decreased (p<0.05) Enterobacteriaceae counts. The liver of birds fed T4 and T6 had higher IGF-I expression compared to other treatments while T6 had higher GHR mRNA expression compared to other treatments. It can be concluded that the addition of postbiotics and inulin had benefical effects on total body weight, feed efficiency, and expression of IGF-I and GHR mRNA in broiler chickens.